STRENGTHENING LOCAL ECONOMY THROUGH COLLABORATIVE GOVERNANCE IN BANGSRI TOURISM VILLAGE, BLORA - Johnsen Hezron Gelora Kasih; Augustin Rina Herawati; Retno Sunu Astuti (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Bangsri Village, located in Blora Regency, achieved 13th place out of 2,500 villages in the 2023 Nusantara Tourism Village Competition and has progressed from a disadvantaged village to a developing village on its way to becoming an advanced one. This accomplishment was achieved despite Bangsri lacking prominent natural tourism attractions such as mountains, rivers, or unique scenic views, and previously being categorized as an underdeveloped and extremely poor village. Through a collaborative governance process involving multiple actors, Bangsri Village succeeded in transforming and developing its tourism potential. This study aims to analyze the collaboration process among stakeholders in developing Bangsri Tourism Village and its contributions to social and economic changes in the village. Employing a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and document analysis. The findings show that collaboration among the Village Government, the youth group Tim Maju Mapan, and local investors was key to success. This collaboration met the five indicators of collaborative governance proposed by Ansell & Gash: face-to-face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes. Evidence of success includes increased community participation, the creation of over 150 jobs, and the return of migrant villagers to invest in their hometown. These findings demonstrate that strong collaboration can turn limitations into strengths and accelerate development based on local potential. It is recommended that the Bangsri Village Government establish a structured collaborative forum and develop guidelines for sustainable tourism investment to strengthen governance and long-term stakeholder commitment.